Australian Psychiatrists' Support for Psychiatric Advance Directives: Responses to a Hypothetical Vignette. Issue 1 (2nd January 2017) - Sellars, Marcus; Fullam, Rachael; O'Leary, Catherine; Mountjoy, Rachel; Mawren, Daveena; Weller, Penelope; Newton, Richard; Brophy, Lisa; McEwan, Troy; Silvester, William
Abstract : This study examines whether Australian psychiatrists would support requests in a psychiatric advance directive (PAD) and the reasons underlying their decisions in response to a hypothetical vignette. An online survey was completed by 143 psychiatrists. Fewer than 3 out of 10 psychiatrists supported the patient to create a PAD which requested cessation of pharmacotherapy (27%) or remaining out of hospital and not being subject to an involuntary treatment order (24%) should their depression condition deteriorate. A thematic analysis showed that patient autonomy was the strongest theme among those who supported the patient to create a PAD, whereas the clinical profile of and risk to the patient and the professional or ethical imperative of the psychiatrist were strongest among those who were unsure about supporting the patient or who did not support the patient. These findings provide a challenge about how to fulfil obligations under the United Nations Convention on the Rights of Persons with Disabilities (2006).